Physicochemical and functional characterization of trupillo flour (Prosopis juliflora (Sw.) DC) and its inclusion in a food matrix (2021)
Introduction— The high protein content has made legumes a raw material of interest in the formulation of different agroindustrial products; the trupillo (Prosopis juliflora) tree is an easily accessible, multipurpose, wild legume that can be used in all its composition, has a high protein value and little commercial level, which is currently being wasted as it is mistakenly considered a weed and that It could be seen as a new alternative that helps in the potentialization of the food sector. Objective— This research aims to functionally characterize trupillo flour (Prosopis juliflora), obtained from leaves and seeds, to include it in a food matrix as a protein extender. Methodology— The experimental design for this research required three phases, i) obtaining, bromatological and functional characterization of leaf flour and trupillo seeds, ii) standardization of formulations for artisan sausages using trupillo flour as a protein source, and iii) bromatological and sensory characterization of the processed sausages. Results— It was found that the flours obtained preserved the characteristic odor and color of each raw material. Particularly, the seed flour presented bromatologically and functionally better protein contents (27.7%), ash (8.04%), swelling capacity (16.7 ml water / g sample), water absorption (7.89 g water / g sample) and water retention capacity (27.9 g water/g sample), for which it was selected to be included in the sausages. In the three formulations made (C, CT and T), there were variations in the color and texture of the sausages, with Formulation T standing out for presenting higher protein content (13.7%). However, consumers preferred Formulation C. Conclusions— These results allow to propose the inclusion of sausage with trupillo flour in the human diet as an alternative to traditional products.